2010
DOI: 10.1016/j.nima.2010.04.059
|View full text |Cite
|
Sign up to set email alerts
|

Experimental observations of in situ secondary electron yield reduction in the PEP-II particle accelerator beam line

Abstract: Beam instability caused by the electron cloud has been observed in positron and proton storage rings and it is expected to be a limiting factor in the performance of the positron

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Where lower SEY are desired it seems that the only possibility to use Al vacuum chambers for accelerator rings is to coat the inner walls with a stable thin film of a low max material, suitable to hinder the interaction of the Al surface with the oxidizing species that inevitably develop during machine running. A similar strategy was also suggested by preliminary studies performed in the Positron low-energy ring of the PEP-II accelerator [8].…”
Section: B Effect Of the Surface Oxidation On Seymentioning
confidence: 83%
See 3 more Smart Citations
“…Where lower SEY are desired it seems that the only possibility to use Al vacuum chambers for accelerator rings is to coat the inner walls with a stable thin film of a low max material, suitable to hinder the interaction of the Al surface with the oxidizing species that inevitably develop during machine running. A similar strategy was also suggested by preliminary studies performed in the Positron low-energy ring of the PEP-II accelerator [8].…”
Section: B Effect Of the Surface Oxidation On Seymentioning
confidence: 83%
“…For other technical surfaces as TiN and Cu [6][7][8]12,13] it has been observed that electron conditioning reduces the high max values measured on the as-received samples to values of the order of 1.3 or even lower, and this behavior has been related to the desorption of contaminants as well as to the formation of a graphitic film upon the interaction of the electron beam with C containing surface adsorbates. For the PETRA III Al alloy sample, however, in spite of the large quantity of C at the surface, a similar growth of a graphitic layer has not been observed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Various types of methods have been proposed, studied and experimentally verified in order to provide a solution to the e-cloud problems. There are two basic approaches for suppressing the ecloud effects: the first one is to modify the chamber surface properties thus reducing the Secondary Emission Yield (SEY) by the application of surface coatings [25][26][27][28][29][30][31][32][33] or by an artificial surface roughness, like grooves [32,[34][35][36][37]. Also the conditioning of the vacuum chamber surfaces by exposing it to synchrotron radiation or generated e-cloud (scrubbing) can partially reduce the SEY [30,33,38,39].…”
mentioning
confidence: 99%